2012 5th IAPR International Conference on Biometrics (ICB) 2012
DOI: 10.1109/icb.2012.6199771
|View full text |Cite
|
Sign up to set email alerts
|

Towards automated caricature recognition

Abstract: This paper addresses the problem of identifying a subject from a caricature. A caricature is a facial sketch of a subject's face that exaggerates identifiable facial features beyond realism, while still conveying his identity. To enable this task, we propose a set of qualitative facial features that encodes the appearance of both caricatures and photographs. We utilized crowdsourcing, through Amazon's Mechanical Turk service, to assist in the labeling of the qualitative features. Using these features, we combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 28 publications
(43 reference statements)
0
53
0
Order By: Relevance
“…Detected facial attributes can be applied directly to authentication. Facial attributes have been applied to enhance face verification, primarily in the case of cross-modal matching, by filtering [19,54] (requiring potential FRF matches to have the correct gender, for example), model switching [18], or aggregation with conventional features [27,17]. [21] defines 65 facial attributes and proposes binary attribute classifiers to predict their presence or absence.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Detected facial attributes can be applied directly to authentication. Facial attributes have been applied to enhance face verification, primarily in the case of cross-modal matching, by filtering [19,54] (requiring potential FRF matches to have the correct gender, for example), model switching [18], or aggregation with conventional features [27,17]. [21] defines 65 facial attributes and proposes binary attribute classifiers to predict their presence or absence.…”
Section: Related Workmentioning
confidence: 99%
“…Because we establish the equivalence between tensor factorisation and gated neural network architecture, our method is scalable to big-data through efficient mini-batch SGD-based learning. In contrast, kernel-based non-linear methods, such as Kernel LDA [34] and multi-kernel SVM [17], are restricted to small data due to their O(N 2 ) computation cost. At runtime, our method only requires a simple feed-forward pass and hence it is also favourable compared to kernel methods.…”
Section: Scalabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The result outperforms feature-based face-matching techniques, as well as state of the art cross-modal matching techniques that focus on learning a mapping between low-level features without first building an invariant mid-level representation. Moreover, a new dataset combining common forensic [9] and caricature datasets [8] were annotated (≈ 59, 000 annotations in total) to learn and evaluate the proposed cross-modal face representation.…”
Section: Fig 1 Illustration Of Sketch Abstraction Level (Top) and Pmentioning
confidence: 99%
“…As previous research has suggested [20], caricature recognition is enabled by targeting the postulated sparse encoding of predominant facial attributes in the human brain. The facial attributes developed in this project were motivated by such findings, and expand on other research related to matching caricatures to photographs [10]. Section 4 discusses the development of these attributes, the use of crowd sourced annotation to label a corpus of data, and provides an analysis of the consistency and discriminability of the choosen attributes.…”
Section: Introductionmentioning
confidence: 99%